The russian ultranationalist movement on the internet: actors, communities, and organization of joint actions - Zuev, D. (Post-Soviet Affairs, 2011)
In 2000, the Russian ultranationalist movement began a new developmental phase, marked by extensive use of the Internet for communication and organization. A social movement analytic framework is used to consider the structure of the movement's web space. The World Wide Web is the data source for investigating the movement's use of the Internet to organize itself and its alternative knowledge production, identifying the ideological content of the movement's main actors and web communities, and examining a central movement actor. The mechanism of knowledge production in this social movement and its organizational culture are explored in the Russian context and as part of larger extreme-right trends.